Proceso de atención de enfermería en paciente adulto mayor con hemorragia gastrointestinal. - Chiliquinga Nuela, Amanda Anabel (2021)
This case analysis refers to upper digestive bleeding in an older adult, taking into account that one of the greatest risk factors for suffering from this disease is age, as well as harmful habits that the patient has or had. Gastrointestinal bleeding is defined as the extravasation of blood that occurs at the level of the digestive tract to the anus and that can manifest in various ways such as melena, hematemesis, hematochezia, rectorrhagia among others, for this reason it is important to control hemodynamic stability since the patient appears anemic, with altered vital signs. The first step to prevent possible complications is the control of blood volume, laboratory examination, constant monitoring of vital signs, in addition to drug treatment as the first key to action is the protection of the intestinal mucosa from stomach acid by means of inhibitors of the proton bomb. The nursing role also plays an important role in the prompt recovery of the patient since individualized care will be provided in order to maintain their altered values within normal limits. The nursing care process not only focuses on the disease but on everything that has to do with the patient, family and environment, covering the needs and at the same time promoting and preventing as well. A very important tool in nursing work is the assessment of functional patterns, reaching a comprehensive understanding about the patient and not only about the disease he or she suffers.